Practices of herbal management of malaria among trading mothers in Shai Osudoku District, Accra. - Evans Osei Appiah; Stella Appiah; Ezekiel Oti-Boadi; Albert Oppong-Besse; Dorothy Baffour Awuah; Priscilla Ofosuhemaa Asiedu; Lt Emmanuel Oti-Boateng (PLoS ONE)
Background Malaria is one of the leading causes of morbidity in the world. It is a significant health concern in most developing countries, including Ghana. Even though there are several orthodox medications used for decades in treating malaria effectively, a substantial number of individuals in developing countries are resorting to the use of herbs in the treatment of malaria. The study aim at exploring the practices of herbal management of malaria among trading mothers in Shai Osudoku District, Accra. Methods A qualitative approach with an exploratory, descriptive design was adopted in analyzing the research problem. Purposive sampling technique was used to select twenty (20) participants to partake in a face-face interview, guided by a semi-structured interview guide. The data were transcribed verbatim and analysed by adopting content analysis. Results Two significant themes and seven subthemes were generated following the analysis of this study. The main themes were; preferences for herbal malaria treatment and the practices and effectiveness of herbal medicine used for malaria treatment. It was worth noting that the women's cultural beliefs did not influence their preference for herbal malaria treatment. The main challenge associated with the herbal malaria treatment was inappropriate dosage specification. Conclusion This study discovered that several factors influenced participants' preferences for malaria treatment. Participants further listed some traditional ways of treating malaria which implies that there is herbal malaria practice. However, literature in this area is inadequate, and most herbs lack specifications for use. It is therefore recommended that future research focus on scientific herbal malaria treatment. Also, regulating bodies should ensure that quality herbal drugs are sold for consumption.